(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article according to Ulas Samchuk’s little known literary-critical and publicistic prose, the author examines his aesthetic views, the meaning of the notions great literature and mass literature in the writer’s aesthetic conception. The author proved that Ulas Samchuk in his works opposed great literature (classical literature) to mass literature, the magnificent example of which he considered to be the works of socialistic realism.